Ricerca e formazione alle professioni educative e formative - Riva, Maria Grazia (Studi sulla Formazione/Open Journal of Education, 2010)
The author argues that it is an important issue in education today to reflect on the training, university and non-professions education and training. We must ask ourselves how and what the size, the theory and practice of research to be a constituent part of the profession of teacher training. The search must then be placed in the same disciplinary teaching of each discipline, in the very way in which we deal with the contents, of whatever kind they are, must pass through a certain style of teaching that identifies the ‘posture’ research in voltage not to go as exhaustive and closed the knowledge that is taught of the qualifying points. The author considers both qualitative and quantitative assessment tools considering how the case studies can be useful to reflect on the emotional scope of the profession of education.